2016
DOI: 10.1007/s10163-016-0522-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic coagulant addition under hydrothermal treatment on the dewatering performance of excess sludge with various dewatering conditions

Abstract: A study for producing low moisture content sludge cake was performed by adding NaCl, CaCl 2 , Ca(OH) 2 , or FeCl 3 to excess sewage sludge under hydrothermal treatment (HT) and varying dewatering conditions from low to high pressure (0.04-12 MPa). FeCl 3 addition under HT resulted in cakes with significantly lower moisture content than HT cakes, and moreover, than raw sludge cakes, under all dewatering conditions. The addition of CaCl 2 produced similar effects to FeCl 3 addition but at weaker extents. The add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The development of efficient and environmentally friendly sludge conditioning agents and the rational use of various sludge conditioning methods in combination with conditioning is an urgent task. Sludge conditioning is the use of physical, chemical, and biological methods to reduce the water content of sludge by applying energy or chemical reagents to the sludge, destroying the floc structure, changing the surface structure and charge of the floc mud, and weakening the interaction between the mud particles to create sufficient conditions for to create the subsequent sludge dewatering while releasing part of the intracellular water and pore water from the sludge [9]. The sludge conditioning process can be divided into physical and pore water processes.…”
Section: Introductionmentioning
confidence: 99%
“…The development of efficient and environmentally friendly sludge conditioning agents and the rational use of various sludge conditioning methods in combination with conditioning is an urgent task. Sludge conditioning is the use of physical, chemical, and biological methods to reduce the water content of sludge by applying energy or chemical reagents to the sludge, destroying the floc structure, changing the surface structure and charge of the floc mud, and weakening the interaction between the mud particles to create sufficient conditions for to create the subsequent sludge dewatering while releasing part of the intracellular water and pore water from the sludge [9]. The sludge conditioning process can be divided into physical and pore water processes.…”
Section: Introductionmentioning
confidence: 99%
“…These cases suggest a high -temperature sintering for fly ash stabilization. Moreover, the heavy metal chloride is more likely to volatilization at high temperature [ 41 ]. Fortunately, it had been reported that certain sintering additives could decrease the melting point of sample.…”
Section: Introductionmentioning
confidence: 99%